Young Adults and Their Finances: An International Comparative Study on Applied Financial Literacy. (8th December 2017) - Oehler, Andreas; Horn, Matthias; Wendt, Stefan; Reisch, Lucia A.; Walker, Thomas J.
Abstract : Recent years have brought a gradual shift of responsibility for pension provisions, financial planning, health care and various insurances from governmental institutions and firms to individuals. To tackle this challenge, individuals need applied financial literacy and not merely theoretical knowledge about financial products and mechanisms that does not reflect real‐life situations. We survey 448 business students in Canada, Denmark, Germany and Iceland to examine how financial literacy is expressed in their financial portfolios. We contrast these findings with the respondents' own expectations and needs. The results show that most respondents exhibit good financial literacy as well as a realistic assessment of risk and return and their impact on (financial) well‐being.